Quantitative and qualitative investigation of shunt failure in an in vitro hemorrhagic hydrocephalus model - Ajaz, Shaheer; Faryami, Ahmad; Suhrawardy, Ayman; Harris, Carolyn A. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundPrevious studies on posthemorrhagic hydrocephalus (PHH) reported notable shunt failure rates as high as 45.1% within the first six months of placement. Using the Automated, In Vitro Model for Hydrocephalus Research (AIMS), we investigated the impact of CSF-like diluted blood solution on ventricular catheters and external ventricular drains (EVD) using quantitative (flow and pressure measurements) and qualitative (real-time brightfield video capture) methods.MethodsThe shunt failure criteria were set at greater than or equal to 30 cmH2O such that the experiment was manually terminated if pressure surpassed 30 cmH2O differential pressure at any point within 24 h. To investigate our hypotheses, shunt failure was investigated in nine groups of catheters (n = 4 per group). Saline was utilized to dilute heparinized whole porcine blood to prepare blood-saline solutions at two concentrations of 0.05 and 0.5 volume percent (v/v%). The bulk input flow rate was set at 0.3 mLmin for all samples except where the flow rate was intentionally varied. The rate of pressure increase (pressurization rate) was used in all statistical analyses.ResultsOver 500 h of data were gathered without leaks or ruptures. There was a statistically significant difference in the pressurization rate across blood concentration groups (P = 0.005). All the barium-impregnated and antibiotic-impregnated catheters reached 30 cmH2O threshold at 0.5% concentration. A statistically significant difference was observed in the pressurization rate (P = 0.029). A more pronounced difference was observed between the antibiotic-impregnated ventricular catheters and antibiotic-impregnated EVDs. All four EVDs completed the 24-hour experiment and did not reach the pressure threshold (P = 0.029).ConclusionA direct relationship was observed between blood concentration and the pressurization rate, such that shunts and EVDs that were exposed to higher concentrations of blood consistently reached 30 cmH2O threshold while the samples in the low-concentration groups did not. In contrast, a reverse relationship was observed between bulk flow rate and pressurization rate, such that the samples exposed to 0.5% at 0.7 mLmin had a significantly smaller pressurization rate than samples exposed to 0.5% at 0.3 mLmin (P = 0.029). These findings highlight the role of clot formation in PHH shunt obstruction and suggest avenues for improved catheter design or clinical management.